Evaluation of the toxicity and chemical alterations of deoxynivalenol degradation products under ozone treatment. (June 2021) - Yang, Yang; Xu, Yun; Wu, Shang; Qiu, Tianyu; Blaženović, Ivana; Sun, Jiadi; Zhang, Yinzhi; Sun, Xiulan; Ji, Jian
Abstract: Here, we studied the ozonolysis of deoxynivalenol (DON) in saturated aqueous ozone. We found that ozone can play an important role in the oxidation and degradation of DON. The reaction reached its peak within 5 min of treatment, and the degradation rate was approximately 70%. Toxicity analysis (CCK-8 analysis, ROS analysis, and apoptosis analysis) revealed that DON and saturated aqueous ozone treatments did not significantly change the toxicity of degradation products, and both could induce a decrease in the viability of A549 cells. The results of the metabolomics and cytotoxicity analysis were consistent. We used the Q Exactive Focus high-resolution liquid chromatography-mass spectrometry system to identify degradation products. Among the four identified degradation products, only the epoxy groups at the C12, C13 positions of C15 H20 O9 were opened. Because the epoxy groups at the C12, C13 positions in most degradation products were not opened based on the toxicity mechanism of DON, the toxicity of DON was not significantly reduced. Highlights: A mechanism of DON degradation by saturated aqueous ozone was clarified. Ozone oxidizes the three hydroxyl groups at C3, C7 and C15 of DON, and open the epoxy at C12, C13. Four degradation products of DON were speculated. The relationship between the structure and cytotoxicity of the products was characterized at the same time point.